Organ size control is dominant over Rb family inactivation to restrict proliferation in vivo - Ehmer, Ursula (2014)
In mammals, a cell’s decision to divide is thought to be under the control of the Rb/E2F pathway. We previously found that inactivation of the Rb family of cell cycle inhibitors (Rb, p107, and p130) in quiescent liver progenitors leads to uncontrolled division and cancer initiation. Here we show that, in contrast, deletion of the entire Rb gene family in mature hepatocytes is not sufficient for their long-term proliferation. The cell cycle block in Rb family mutant hepatocytes is independent of the Arf/p53/p21 checkpoint but can be abrogated upon decreasing liver size. At the molecular level, we identify YAP, a transcriptional regulator involved in organ size control, as a factor required for the sustained expression of cell cycle genes in hepatocytes. These experiments identify a novel, higher level of regulation of the cell cycle in vivo, in which signals regulating organ size are dominant regulators of the core cell cycle machinery.